Factors affecting trapping success of northern bobwhites in the rolling plains of Texas. (12th August 2016) - Ruzicka, Rebekah E.; Rollins, Dale; Lacoste, Lloyd M.; Wester, David B.
ABSTRACT: Trapping of northern bobwhites ( Colinus virginianus ) is commonly conducted for research purposes. We investigated the influence of weather, lunar phase, time of day, and season on bobwhite trapping success in the Rolling Plains ecoregion of Texas, USA, from 2009 to 2011. We trapped bobwhites in autumn (Oct–Nov) and spring (Feb–Mar) using walk‐in funnel traps baited with sorghum. We used a negative binomial regression to examine effects of temperature, humidity, wind speed, lunar phase, time of day, season, the number of traps set, and year on the number of bobwhites captured per trapping session. More bobwhites were trapped during the spring, in the evenings, and when temperatures were cooler. There was also some evidence for an influence of lunar phase on the number of bobwhites captured with greater counts during the new moon and third quarter. These variables may be important to consider for maximizing catch‐per‐unit‐effort, when using trapping data to estimate relative abundance, or when conducting mark–recapture studies. © 2016 The Wildlife Society.